Drug-Coated Balloon Treatment of Femoropopliteal Lesions Typically Excluded From Clinical Trials: 12-Month Findings From the IN.PACT Global Study. (December 2018) - Ansel, Gary M.; Brodmann, Marianne; Keirse, Koen; Micari, Antonio; Jaff, Michael R.; Rocha-Singh, Krishna; Fernandez, Eric J.; Wang, Hong; Zeller, Thomas; ,
Purpose: To report a post hoc analysis comparing outcomes between subjects who would have been included in the IN.PACT SFA randomized controlled trial vs those who would have been excluded.Methods : The 1406 subjects enrolled in the IN.PACT Global Study ( ClinicalTrials.gov identifier NCT01609296) were retrospectively assigned to a standard-use group (n=281) based on the inclusion and exclusion criteria from the randomized IN.PACT SFA trial; the remaining 1125 patients were assigned to the broader-use group. Freedom from clinically-driven target lesion revascularization (CD-TLR) was evaluated at 12 months. The composite primary safety endpoint was freedom from 30-day device- and procedure-related death plus freedom from 12-month target limb major amputation and clinically-driven target vessel revascularization (CD-TVR). Functional outcomes were evaluated with dedicated questionnaires.Results: Compared with the standard-use cohort, the broader-use lesions were longer, more calcified, and had more popliteal involvement, bilateral disease, and in-stent restenosis (p<0.001 for all). Freedom from 12-month CD-TLR by Kaplan-Meier analysis was 96.6% for the standard-use group and 91.6% for the broader-use group (p=0.005). The safety endpoint was 96.2% in the standard-use group and 91.0% in the broader-use group (p=0.003). The 12-month CD-TLR (3.4% standard-use vs 8.5% broader-use, p=0.004) and CD-TVR (4.2% standard-use vs 9.1% broader-use, p=0.008) were increased in the broader-use group. Twelve-month all-cause mortality was not increased (3.8% standard-use vs 3.4% broader-use, p=0.852).Conclusion: Post hoc analysis of the IN.PACT Global Study of real-world patients demonstrated consistent outcomes with significant clinical improvement to 12 months in subjects with complex lesions typically excluded from a randomized controlled trial.